Prospects for tin-containing halide perovskite photovoltaics - Hu, S; Smith, JA; Snaith, HJ; Wakamiya, A (American Chemical Society, 2023)
Tin-containing metal halide perovskites have enormous potential as photovoltaics, both in narrow band gap mixed tin–lead materials for all-perovskite tandems and for lead-free perovskites. The introduction of Sn(II), however, has significant effects on the solution chemistry, crystallization, defect states, and other material properties in halide perovskites. In this perspective, we summarize the main hurdles for tin-containing perovskites and highlight successful attempts made by the community to overcome them. We discuss important research directions for the development of these materials and propose some approaches to achieve a unified understanding of Sn incorporation. We particularly focus on the discussion of charge carrier dynamics and nonradiative losses at the interfaces between perovskite and charge extraction layers in p-i-n cells. We hope these insights will aid the community to accelerate the development of high-performance, stable single-junction tin-containing perovskite solar cells and all-perovskite tandems.